Pavel Cheche interview and stories - Pavel Cheche; Valentina Dedyk (Alexander King, 2013)
Pavel Cheche talks a bit about himself, tells a myth or two and some remembrances from childhood and what elders taught him. Engaging storyteller, nice guy, beautiful language. The room was a small office in Institute for Teacher Advancement. Danced with Mengo under Gil, then was one of 3-4 veterans to start Angt with Iosef Zhukov. Now Assistant Director of Angt. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.